1997
DOI: 10.1007/bf02445045
|View full text |Cite
|
Sign up to set email alerts
|

Subsynaptic units as a universal system-forming and regulating factor of brain synapses

Abstract: Dense projections and postsynaptic density --specialized structures of the synaptic cytoskeleton --are regarded as a single functional system of subsynaptic units. From this viewpoint, interneuronal relations in health and after brain ischemia are analyzed. It is shown that hyperplasia and recombination of the system of subsynaptic units are the major mechanisms responsible for reorganization of functionally mature interneuronal junctions in the mammalian and human brain. Key Words: synapse; synaptic cytoskele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
(141 reference statements)
0
3
0
Order By: Relevance
“…This phenomenon of the transformation of synapses was found in electron microscopic experiments during 90 minutes of severe hypoxia [144,145]. It was shown that the change of a morphological type occurs due to the changes in the area, density and configuration of the network elements of the presynapses and in their configuration [153]. Almost all of these parameters can affect the density of the presynapses.…”
Section: Biochemical Equivalents Of the Morpho-structural Reorganizatmentioning
confidence: 87%
See 1 more Smart Citation
“…This phenomenon of the transformation of synapses was found in electron microscopic experiments during 90 minutes of severe hypoxia [144,145]. It was shown that the change of a morphological type occurs due to the changes in the area, density and configuration of the network elements of the presynapses and in their configuration [153]. Almost all of these parameters can affect the density of the presynapses.…”
Section: Biochemical Equivalents Of the Morpho-structural Reorganizatmentioning
confidence: 87%
“…Both the cholinergic projective systems and interneurons of the rat cortex and hippocampus are actively involved in learning and memory processes in the Morris water maze model [28]. The presynapses of cholinergic interneurons in the cat temporal associative cortical area do not participate in inherited abilities for the analysis of images [25] but all of other associative cortical areas (frontal and parietal) active participated in cognitive processes [153].…”
Section: Cholinergic Organization Of Brain Functions Under Normal Conmentioning
confidence: 99%
“…Sommer sector remained intact with a strong ability to slow the accumulation and storage preservation of information [2], which provokes the appearance of sustained foci of excitation, by activation of additional neurons in volleys of activity in the hippocampus [1], combining hyperactive neurons in generating the strong excitation [10] by fi xing all kinds of sensory input [3]. Diffuse reorganization of hippocampal neural circuits alters intercentral relationships in brain structures.…”
Section: Resultsmentioning
confidence: 99%